APLIKASI PENDAFTARAN DAN PENERIMAAN DATA PERSYARATAN CALON ANGGOTA LEGISLATIF SEMENTARA SECARA ONLINE PADA PARTAI KEADILAN SEJAHTERA DI KABUPATEN BENGKALIS - Rofiqoh, Ummi; Irawan, Yuda; Melyanti, Rika (Riau Journal Of Computer Science, 2020)
Currently, the process of registering and receiving data on the requirements for legislative candidates to the Bengkalis Regency Prosperous Justice Party is still being carried out conventionally. So that each prospective member of the PKS party must submit directly the required data in the form of sheets of paper or documents. To solve this problem, it is proposed that the Application for Registration and Acceptance of Data Requirements at the Sejatera Justice Party in Bengkalis Regency uses the programming language PHP and MySQL as a database using the waterfall method which can be computerized so that it becomes faster and more accurate. This application has two parts, namely the admin of the political party, who works in the section on the requirement data for each candidate for legislative member of the PKS Party, and each candidate for the legislative member itself to input the required data. This application has a print feature of data that has been input by each prospective member, and also party data that can be printed by the PKS party, namely Model B, Model B1, Model B2, and Model B3 data , while the data that can be printed by each prospective member are Model.BB1, Model.BB2, which are implemented in pdf format. In addition, in this application, prospective members of the PKS party can view data information that has not been completely filled in